2022
DOI: 10.3390/nano12020236
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Metal-Organic-Framework Derived Nanocages into a Microcapsule for Shuttle Effect-Suppressive Lithium-Sulfur Batteries

Abstract: Long-term stable secondary batteries are highly required. Here, we report a unique microcapsule encapsulated with metal organic foams (MOFs)-derived Co3O4 nanocages for a Li-S battery, which displays good lithium-storage properties. ZIF-67 dodecahedra are prepared at room temperature then converted to porous Co3O4 nanocages, which are infilled into microcapsules through a microfluidic technique. After loading sulfur, the Co3O4/S-infilled microcapsules are obtained, which display a specific capacity of 935 mAh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The efficacy of Ga 12 As 12 for adsorbed hydrogen molecules is intrinsically studied by considering the FMO, which is fundamentally constituted by the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO). 53 The HOMO−LUMO orbital describes the electronic structure and reveals the flexibility of the electron transition from the valence band to the conduction band. 54 This also includes the tendency to donate and accept electrons, with the HOMO orbital having a higher tendency to donate and the LUMO having a higher tendency to accept electrons.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…The efficacy of Ga 12 As 12 for adsorbed hydrogen molecules is intrinsically studied by considering the FMO, which is fundamentally constituted by the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO). 53 The HOMO−LUMO orbital describes the electronic structure and reveals the flexibility of the electron transition from the valence band to the conduction band. 54 This also includes the tendency to donate and accept electrons, with the HOMO orbital having a higher tendency to donate and the LUMO having a higher tendency to accept electrons.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…At the outlet, the inner phase will be wrapped by the outer phase which formed the microcapsules continuously under the shear action of the driving fluids. [ 113 ] The same concept of coaxial droplet microfluidics has been applied to fabricate metal–organic framework‐derived nanocage microcapsules [ 114 ] and polysulfide‐confined all‐in‐one porous microcapsules ( Figure a) [ 115 ] for lithium–sulfur battery cathodes, with the latter achieving a high capacity of 1025 mAh g −1 and stable cycling life of 700 cycles. [ 115 ] Moving to sodium‐ion batteries, Zheng et al proposed a microfluidic reactor method of fabricating sodium vanadium fluorophosphate (Na 3 V 2 O 2 (PO 4 ) 2 F) for sodium‐ion battery cathodes (Figure 7b).…”
Section: Energy Materials Fabricated By Microfluidic Techniquesmentioning
confidence: 99%
“…[34] Liu et al reported that microcapsules encapsulated with metal-organic frameworks (MOFs)-derived Co 3 O 4 nanocages provided high coulombic efficiency and rate performance in the LiÀ S batteries. [35] While many studies have reported the effect of carbon type on the electrochemical performance of LiÀ S batteries, there is an astonishingly limited understanding of the effect of carbon properties on the battery's cell-and system-level performance. Herein, we investigated the impact of S loading and carbon type on the electrochemical, cell-and system-level performance of the LiÀ S battery by employing experimental and modeling methods together.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. reported that microcapsules encapsulated with metal‐organic frameworks (MOFs)‐derived Co 3 O 4 nanocages provided high coulombic efficiency and rate performance in the Li−S batteries [35] …”
Section: Introductionmentioning
confidence: 99%